Sports marketing-a pioneering style of marketing management - B M, RAJA SEKHAR (Journal of Management and Science, 2021)
Now a day’s Sports marketing became as a subdivision of marketing which focuses on the promotion of sports and also teams as well as the promotion of products and services through sporting events and sports teams. This is a service where the element promoted can be a physical product or a brand name.